Persons with Intellectual Disability and Access to Justice in Nigeria: Challenges and the Way Forward - Augustine Edobor Arimoro (Faculty of Law, Hasanuddin University, 2019)
Conservatively, there are approximately about two million persons in Nigeria who may be referred to as persons with intellectual disabilities. These persons suffer from several challenges ranging from economic to non-inclusion in the society. In the paper, the discussion focuses on persons with intellectual disabilities and the effective access to justice as a fundamental right. The paper finds that even though Nigeria has adopted and ratified the United Nations Convention on the Rights of Persons with Disabilities, the Federal Government of Nigeria has not been proactive in supporting the persons with disabilities in the country to enjoy these rights. Furthermore, despite the provision in the 1999 Constitution of the Federal Republic of Nigeria to ensure freedom from discrimination, there is no direct effect on procedure to ensure that the rights of the disabled persons are protected. The paper proposes for a framework for the protection of the person with intellectual disability which includes legal protection, legal awareness, legal aid, adjudication and for civil society oversight of the access of persons with intellectual disabilities to justice.